2016
DOI: 10.1111/chd.12437
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter closure of calcified patent ductus arteriosus in older adult patients: Immediate and 12-month follow-up results

Abstract: Successful closure of calcified PDA with few complications in older adult patients was achieved using the duct occluder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
1
6
1
Order By: Relevance
“…is is a well-described difficulty among elderly patients with PDA [3,18] and, as in our cohort, more frequently appears among calcified ducts.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…is is a well-described difficulty among elderly patients with PDA [3,18] and, as in our cohort, more frequently appears among calcified ducts.…”
Section: Discussionsupporting
confidence: 68%
“…Residual shunts and haemolysis are more frequently found in percutaneously closed calcified ducts [3]. However, a small residual shunt in only one patient at follow-up (VSO, calcified duct) and no case of haemolysis were found in our analysis.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…IVUS precisely revealed that calcification was around 180 at the aortic side. The size of the occluder we selected was twice that of the narrowest portion of the PDA, which was acceptable based on a previous report [5]. Surgical findings and a contrast computed tomography scan after urgent surgery clearly showed an intramural hematoma and that the dissection cavity started from the periphery of the device; therefore, the device was suspected to be related to this event.…”
Section: Discussionmentioning
confidence: 94%
“…Wider and longer PDA and B/D type-PDA may necessitate longer procedural/fluoroscopic times. 4,7) Calcification reduces duct elasticity, leading to difficulty in using the antegrade approach (passing the catheter from the pulmonary artery to the descending aorta), and, thus, a retrograde approach (wire-assisted technique) is sometimes needed, leading to longer procedural/fluoroscopic times 14) : one patient in the study group needed it. Even with this background, the study group showed shorter fluoroscopic/procedural times, which may suggest that the 3D model made the procedure easier.…”
Section: Discussionmentioning
confidence: 99%